Pengaruh Citra Merek dan Persaingan Pangsa Pasar Pada Gadget Merek Apple Terhadap Minat Beli Di Indonesia - Muhammad Zulfikar Romadhon; Damar Putranto; Rayhan Gunaningrat (Jurnal Riset dan Inovasi Manajemen, 2024)
It seems that the world of communication today cannot be separated from technology. The use of communication technology makes it increasingly sophisticated. Every year, even every month, gadget companies always innovate their products with the aim of attracting consumer buying interest. Brand awareness and market share are closely related in the world of marketing. This study aims to identify and analyze the impact of brand image and market share competition on consumer purchasing interest in Indonesia. Data collection uses a quantitative approach using an associative explanatory survey method with data collection techniques used namely questionnaires, observation and interviews. The number of samples used in this research was 99 respondents. The results of the research study are that the use of brand image in Apple products has a strong level of influence on consumer behavior.